Qualification and implementation of line ratio spectroscopy on helium as plasma edge diagnostic at ASDEX Upgrade. (14th December 2017) - Griener, M; Burgos, J M Muñoz; Cavedon, M; Birkenmeier, G; Dux, R; Kurzan, B; Schmitz, O; Sieglin, B; Stroth, U; Viezzer, E; Wolfrum, E
Abstract: A new thermal helium beam diagnostic has been implemented as plasma edge diagnostic at the ASDEX Upgrade (AUG) tokamak. The helium beam is built to measure the electron density n e and temperature T e simultaneously with high spatial and temporal resolution in order to investigate steady-state as well as fast transport processes in the plasma edge region. For the thermal helium beam emission line ratio spectroscopy, neutral helium is locally injected into the plasma by a piezo valve. This enabled the measurement of the line resolved emission intensities of seven Hei lines for different plasma scenarios in AUG. The different line ratios can be used together with a collisional-radiative model (CRM) to reconstruct the underlying electron temperature and density. Ratios from the same spin species are used for the electron density reconstruction, whereas spin mixed ratios are sensitive to electron temperature changes. The different line ratios as well as different CRMs are tested for their suitability for diagnostic applications. Furthermore their consistency in calculating identical parameters is validated and the resulting profiles are compared to other available diagnostics at AUG.